Psychology of Terrorism and the Staircase Mataphor - Josef Smolík (Vojenské rozhledy, 2015)
The article deals with the contemporary form of terrorism, introduces selected issues and discusses the psychology of terrorism. Various forms and typologies of contemporary terrorism which occurs in different geographical and cultural areas and uses large scale of methods and tactical and strategic approaches are introduced as well. The main goal of this article is to describe psychological aspects of terrorism with the emphasis on the motivation and group dynamics of terrorist organizations. The staircase metaphor which allows thinking about the process of recruitment of terrorists is introduced as well. The article derives especially from theoretical socio-psychological and political findings.